Analisis Ekstensifikasi Pajak Hotel Atas Rumah Kos Dalam Rangka Meningkatkan Penerimaan Pajak Daerah Pada Unit Pelayanan Pemungutan Pajak Daerah (UPPPD) Grogol Petamburan Kota Administrasi Jakarta Barat Tahun 2022-2023 - Liana Lestari; Mira Permata Sari (Jurnal Ilmu Administrasi Publik, 2025)
This research is inspired by the lack of taxpayer compliance. Thus, many hotel taxes on boarding houses have not been registered so that it affects local tax revenue in the Grogol Petamburan area of the West Jakarta Administrative City. This research is purposed by the author to analyze the extensification of hotel tax on boarding houses in order to increase local tax revenue at the Regional Tax Collection Service Unit (UPPPD) Grogol Petamburan, West Jakarta Administrative City in 2022-2023. As well as knowing the obstacles and efforts in overcoming these obstacles in increasing the realization of hotel tax revenue on boarding houses. This research used qualitative research methods. The data used are primary data obtained from informant interviews and secondary data. Data collection techniques were conducted by interview, observation, documentation, and triangulation. The results showed that the extensification carried out had been quite effective and contributed to increasing the number of boarding house taxpayers from 234 tax objects in 2020 to 285 active tax objects in 2023. In terms of revenue, there was a significant increase, from Rp3.5 billion in 2022 to Rp4.7 billion in 2023. However, the implementation of this policy still faces obstacles such as low tax literacy among boarding house owners, outdated tax object data, and limited use of technology in the registration and reporting process. To overcome these obstacles can use method by improving coordination with the village and RT/RW, expanding direct and digital socialization, and facilitating tax services through online systems. Keywords Analysis, Extensification, Hotel Tax, Hotel Tax on Boarding Houses, Tax Revenue